PENGENDALIAN KUALITAS PADA AGROINDUSTRI GULA DENGAN METODE FAILURE MODE AND EFFECT ANALYISIS (FMEA) DI KABUPATEN BONDOWOSO - Mahardika, Nidya Shara; Tyas, Putri Nikita Aprilia Aruming; Adila, Hifdzil (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Jember, 2023)
The sugar agroindustry in Bondowoso, particularly PG Pradjekan, is a part of the business unit of PTPN XI that focuses on sugarcane processing. Its main product is white crystalline sugar, which must adhere to the Indonesian National Standard (SNI), with quality characteristics measured through sugar solution color (ICUMSA) and Grain Size (BJB). The quality of the produced white crystalline sugar is maintained through a monitoring process to ensure compliance with government-established standards.Quality monitoring involves control over ICUMSA and BJB, with the understanding that a smaller BJB results in a whiter ICUMSA, indicating better quality. The efforts in quality control aim to assist the company in maintaining and enhancing product quality in accordance with government standards. The company's target is to achieve zero defects, with a tolerance of 0.5%.Data from the milling process in 2022 at PG Pradjekan recorded sugar production of 16,693 tons. However, there was a defect rate of 0.92% of the total production, equivalent to 155 tons. These defects incur losses for the company as rejected products undergo reprocessing, leading to increased costs and prolonged production time. Therefore, improving quality control is crucial to reducing defect rates and enhancing overall production efficiency.